2018
DOI: 10.2217/epi-2018-0002
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Hsa_Circ_0072995 Promotes Breast Cancer Cell Migration and Invasion Through Sponge for Mir-30c-2-3p

Abstract: Hsa_circ_0072995 may be a novel biomarker for breast cancer, and may function in metastasis of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 34 publications
0
41
1
Order By: Relevance
“…19 Analogously, up-regulation of hsa_cir-cRNA_0072995 is determined in breast cancer cells; in contrast, the silencing of hsa_circRNA_0072995 restrained aggressive malignant behaviours in breast cancer. 20 Moreover, hsa_circRNA_002178 silencing inhibited inflammation in vivo through reducing TNF-α and IL-6 levels and prevented tumour growth. Targeting angiogenesis or inflammation before clinical manifestation is in favour of preventing tumour growth and progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Analogously, up-regulation of hsa_cir-cRNA_0072995 is determined in breast cancer cells; in contrast, the silencing of hsa_circRNA_0072995 restrained aggressive malignant behaviours in breast cancer. 20 Moreover, hsa_circRNA_002178 silencing inhibited inflammation in vivo through reducing TNF-α and IL-6 levels and prevented tumour growth. Targeting angiogenesis or inflammation before clinical manifestation is in favour of preventing tumour growth and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Our study conducted hsa_circRNA_002178 loss-of-function experiments and finally identified that hsa_cir-cRNA_002178 functioned as a miR-328-3p sponge and impaired miR-328-3p-targeted repression of COL1A1.The first observation was that high hsa_circRNA_002178 expression in breast cancer was associated with poor prognosis.Knockdown of hsa_circRNA_002178 suppressed aggressive malignant behaviours including cell proliferation and angiogenesis. Analogously, up-regulation of hsa_cir-cRNA_0072995 is determined in breast cancer cells; in contrast, the silencing of hsa_circRNA_0072995 restrained aggressive malignant behaviours in breast cancer 20. Analogously, up-regulation of hsa_cir-cRNA_0072995 is determined in breast cancer cells; in contrast, the silencing of hsa_circRNA_0072995 restrained aggressive malignant behaviours in breast cancer 20.…”
mentioning
confidence: 99%
“…CircRNAs have been recognized as imperative regulators in multiple physiological/pathological processes. Although the exact roles of most circRNAs are still unclear, accumulating evidence has documented that some of them can function as oncogenic or tumor suppressive roles in human malignancies, including BC [7][8][9]. For example, Song et al revealed that silencing of circ_0007534 attenuates BC cell progression via affecting miR-593/MUC19 axis [10].…”
Section: Introductionmentioning
confidence: 99%
“…27 circFBLIM1 plays a vital role in HCC progression. 28 circNT5E functions as an important tumor promoter in glioblastoma tumorigenesis by stimulating tumor proliferation, invasion, migration, and apoptosis, 29 while the circITGA7 can inhibit colorectal cancer growth and metastasis. 30 In terms of potential molecular mechanisms, studies have indicated that circRNAs containing miRNA target sites can serve as miRNA sponges and participate in posttranscriptional regulation of expression.…”
Section: Discussionmentioning
confidence: 99%
“…30 In terms of potential molecular mechanisms, studies have indicated that circRNAs containing miRNA target sites can serve as miRNA sponges and participate in posttranscriptional regulation of expression. For example, hsa_circ_0072995 acts as the sponge of miR-30c-2-3p and promotes breast cancer cell migration and invasion, 29 while circMTO1 suppresses HCC progression by binding to miR-9. 31 hsa_circ_0000337 is located on chr11: 70200406-70202360 with a length of 419 bp and its gene symbol is PPFIA1 (PTPRF interacting protein alpha 1).…”
Section: Discussionmentioning
confidence: 99%